Determination of cyanobacterial cyclic peptide hepatotoxins in drinking water using CE - Birungi, Grace; Li, Sam Fong Yau (Electrophoresis, 2009)
Four cyanobacteria hepatotoxins microcystin LR, microcystin RR, microcystin YR, and nodularin were simultaneously determined in drinking water using CZE and MEKC coupled with UV detection. The toxins were satisfactorily separated in both CZE and MEKC modes. Detection limits were in the range of 0.82–4.81 mg/mL, with R2 values of 0.994–0.999. The linearity range tested for the standards was 5–100 mg/mL and RSD percentages were in the range of 1.0–2.5% for retention time and 3.0–10.2% for peak area. When a known amount of standard was spiked into a known volume of water and extracted, recoveries were 90.3% (RR), 101.5% (nodularin), 90.6% (YR), and 88.2% (LR). The use of SPE enabled cleanup and pre-concentration of a real sample to achieve a 100- fold concentration factor. Detection limits after SPE of the real sample spiked with microcystins were 0.090 mg/L (RR), 0.076 mg/L (YR), and 0.110 mg/L (LR), with RSD percentage values of 9.9–11.7% for peak area and 2.2–3.3% for retention time. The technique developed provides an alternative method for determining microsystems at levels of concentration that will be able to meet WHO drinking water guidelines for microsystems.
Keywords: CE; Microcystin(s; Nodularin